An Experimental Study of the Formation of Talc through CaMg(CO3)2–SiO2–H2O Interaction at 100–200°C and Vapor-Saturation Pressures. (4th July 2017) - Wan, Ye; Wang, Xiaolin; Chou, I-Ming; Hu, Wenxuan; Zhang, Yang; Wang, Xiaoyu
Abstract : The metamorphic interaction between carbonate and silica-rich fluid is common in geological environments. The formation of talc from dolomite and silica-rich fluid occurs at low temperatures in the metamorphism of the CaO–MgO–SiO2 –CO2 –H2 O system and plays important roles in the formation of economically viable talc deposits, the modification of dolomite reservoirs, and other geological processes. However, disagreement remains over the conditions of talc formation at low temperatures. In this study, in situ Raman spectroscopy, quenched scanning electron microscopy, micro-X-ray diffraction, and thermodynamic calculations were used to explore the interplay between dolomite and silica-rich fluids at relatively low temperatures in fused silica tubes. Results showed that talc formed at ≤200°C and low CO2 partial pressures ( P CO2 ). The reaction rate increased with increasing temperature and decreased with increasing P CO2 . The major contributions of this study are as follows: ( 1 ) we confirmed the formation mechanism of Mg-carbonate-hosted talc deposits and proved that talc can form at ≤200°C; ( 2 ) the presence of talc in carbonate reservoirs can indicate the activity of silica-rich hydrothermal fluids; and (3) the reactivity and solubility of silica require further consideration, when a fused silica tube is used as the reactor in high P – T experiments.